Design, development and implementation of a mobile learning strategy for undergraduate medical education - Toro-Troconis,M; Morton,CE; Bennie,T; Leppington,C; Hemani,A; Lupton,M (Journal of EAHIL, 2016)
This paper describes the process of introducing a mobile learning strategy into a medical school by issuing iPadsto clinical students. Data was collected from focus groups, surveys and by engaging a number of student “iPadchampions”. Students had a positive attitude and experience with the iPads for learning and highlighted someareas for improvement particularly for electronic sign-off. Introduction of mobile technology into medical educationis proving to be popular with medical students. Early adoption of mobile technology brings medical students closerto the digital healthcare environment which is rapidly adopting the use of electronic health records, electronic x-ray and laboratory order and online evidence-based practice tools to support patient care.